Past, present and scenario of the future state of ozone above Aкademiк Vernadsky station in Antarctic season of the ozone hole - Martazinova, V. (Ukrainian Antarctic Journal, 2017)
The main objective of the study is development a method for forecasting the state of ozone above the Ukrainian Antarctic Akademik Vernadsky station since 1972 are presented in the article.The result of study of the state of ozone above Vernadsky station from 1972 is given in the article. An analogue to the state of ozone 2016/2017 is found using the similarity criteria from the observations archive of the station. The proposed model of the change in large-scale atmospheric circulation for the Southern Hemisphere is used to predict the state of the ozone over the Vernadsky station in the next decade. Main conclusion from this study is that in the next decade should expect an increase in the total ozone above the station.